THE LIFE AND WORK OF TOXIR RAJABI - San’atjon Sharipov; Borieva Shodiya (Web of Journals Publishing, 2024)
This article is devoted to the life and creative activity of the Uzbek composer, People's Artist and music scientist Toxir Rajabi. It contains information about his childhood, his first steps in the field of music, his contribution to the musical culture of Uzbekistan, his works, pedagogical activity and scientific works. Toxir Rajabi's creativity, enriched with modern styles, while preserving the traditions of national music, occupies an important place in the cultural heritage of our country. The article also provides a brief analysis of his famous works and musical legacy.
Keywords: Toxir Rajabi, Uzbek music, composer, creativity, history of music, pedagogy, national music, cultural heritage, people's artist, works.